Modal Analysis of Power Electronics Module of Spacecraft and its Health Monitoring – An Approach. (2016) - Pandit, Jiwan Kumar; Mahapatra, D. Roy; Pandiyan, R.
Abstract: The spacecraft launch environment is quite harsh which can damage the spacecraft electronics. The high intensity vibrations occurring during this phase are transmitted to the spacecraft structures and its electronic equipment. The high intensity vibrations can be sensed using flexible nano sensors and these inputs could be used by actuators to safeguard the spacecraft electronics.